Experimental and Numerical Study on Hydromechanical Coupled Deformation Behavior of Beishan Granite considering Permeability Evolution - Z. H. Wang; W. G. Ren; Y. L. Tan; Heinz Konietzky (Geofluids)
Beishan granite is a potential host rock for a high-level radioactive waste (HLW) repository in China. Understanding the hydromechanical (HM) behavior and permeability evolution of Beishan granite is important for the HLW repository safety. Therefore, the granite of Beishan in Gansu province was studied. HM coupled tests are carried out on Beishan granite under different pore pressures. The results show that the initial pressure difference has little influence on permeability measurement before dilatancy starts. However, after onset of dilatancy, the permeability increases with the increasing initial pressure difference. The initial permeability of Beishan granite is about 10−18 m2 under a confining pressure of 20 MPa. In the initial loading phase, the permeability shows a relatively large reduction. Then, the permeability almost keeps constant until dilatancy starts. From dilatancy point to peak stress, permeability increases linearly with volumetric strain. The proposed permeability evolution rule is implemented into a numerical code to perform HM coupled simulations. The simulation results show that the damaged zone first appears at the model boundary and then extends to the inside, forming high volumetric strain areas. And it provides seepage channels for fluid flow. The macroscopic fracture patterns indicate that pore pressure accelerates rock degradation during HM coupling. The obtained results help to understand the damage mechanisms of granite caused by pore pressures and are of great importance for the safety of a HLW repository.